Evaluating the privatization experiences of selected countries (United Kingdom, Russia, Arab Republic of Egypt) - الدين, سمية محمود نجم; سعيد, محمد رؤوف (Sulaimani Journal for Humanities, 2019)
Since 1979,many state owned industries in the UK have been sold to private shareholders, Privatization in Russia describes the series of post-soviet reforms that resulted enlarge-scale Privatization state owned assets, particularly in industrial ,energy ,and financial sectors. As for Egypt the openness policy which started in1974necessitated reviving the economy through openness ,especially for foreign investments since these policies started to have more strength and influence after the 1980s and they are continuing to our present time ,it became apparent that the privatization processes in some selected countries showed some successes and many cases of failure hence the study had reached to with some conclusions which can be seen as a road map for the countries intending to privatize some of their state enterprises.